Handbook of research on artificial intelligence applications in literary works and social media - Keikhosrokiani, Pantea; Pourya Asl, Moussa (Hershey, PA : IGI Global, Engineering Science Reference, 2023)
'This handbook presents contemporary developments in the adoption of artificial intelligence in textual analysis of literary works and social media, introducing current approaches, techniques, and practices in data science that are implemented to scrap and analyze text data'--
Includes bibliographical references and index.
Keywords: Text processing (Computer science); Content analysis (Communication) -- Data processing; Social media -- Data processing; Literature -- Data processing; Artificial intelligence; Data mining; Big data